Behaviour of Retaining Wall Founded on Collapsible Soil – A Prototype Laboratory Study - Safa Hussain Abid Awn; Waad Abdulsattar Zakaria (Diyala Journal of Engineering Sciences, 2014)
Retaining walls may be required in a location where gypsum may present in soil in large percentages .The behavior of retaining walls on ordinary soils is well known but the behavior of retaining walls resting on gypseons soils may be not well understood as the case of ordinary soils. In this study it is intended to reflect the behavior of gravity retaining wall resting on collapsible soil. And to do so a small prototype model (600mm*500mm*200mm) is used with soil mixed in presumed percentages with different gypsum percentages (5%, 20%, 30%, 50%). In addition to a model with 30% gypsum and treated with 2.7% Cement dust mixed with soil founded retaining wall structure. After preparing the foundation gypseous soil, a small glass made retaining wall filled with sand, which represent gravity wall, is put over such bed and backfilled with ordinary sandy soil. Dial gauges are placed to side and top of wall to measure the rotation settlement behavior and collapse of system. 4kPa stress are applied to backfill soil as to accelerate collapse with leaching process commenced. Data are recorded and analyzed completely, which shows the behavior of such structures embedded with different gypsum content. The improvement in rotation settlement and collapse for the retaining wall model reaches more than 89%, was gained after treating the embedded gypseous soil layer, with 2.7% cement dust.